1947
DOI: 10.1079/bjn19470008
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Composition of Sow's Milk

Abstract: Most of the scanty literature on the major constituents of sow's milk is old, and nothing has to our knowledge been published on its vitamin composition, with the exception of the fragmentary information about vitamins A and C mentioned below.Probably the main reason for this relative lack of information is the difficulty of obtaining satisfactory samples of sow's milk. This difficulty is stressed in every paper published on the subject, and is connected with the mechanism of the 'let down' o f . milk over whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

1962
1962
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 20 publications
5
14
1
Order By: Relevance
“…The extremely high percent of protein generally associated with colostrum during the first few hours after farrowing was not observed 2 or 3 days after farrowing in the present study. The overall average protein content of 5.60% agrees favorably with other reported values (Braude et al, 1947;Bowland et al, 1949a;Heidebrecht etal., 1951;Smith, 1952Smith, 1959Perrin, 1954Perrin, , 1955Lodge, 1959b;Salmon-Legagneur, 1959;Jylling and Sorensen, 1960).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The extremely high percent of protein generally associated with colostrum during the first few hours after farrowing was not observed 2 or 3 days after farrowing in the present study. The overall average protein content of 5.60% agrees favorably with other reported values (Braude et al, 1947;Bowland et al, 1949a;Heidebrecht etal., 1951;Smith, 1952Smith, 1959Perrin, 1954Perrin, , 1955Lodge, 1959b;Salmon-Legagneur, 1959;Jylling and Sorensen, 1960).…”
Section: Resultssupporting
confidence: 81%
“…Bowland et al (1949a) and Perfin (1955) reported a large reduction in dry matter content during the transition from colostrum to milk. The overall average of 20.2 3 dry matter compares favorably with other reports (Braude et al, 1947;Bowland et al, 1949a;Heidebrecht et al, 1951;Perrin, 1954;Lodge, 1959 a, b;Jylling and Sorensen, 1960).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Our results on IB sow's milk composition are very close and, as lactation advanced, followed a similar pattern to those observed by Klobasa et al (1987) in milk samples from German Landrace sows. Nevertheless, compared with Braude et al (1947), working with Large White sows, the present results show consistently Nutrient balance in suckling Iberian piglets lower concentrations for total solids, fat and protein and a higher lactose content. According to Liotta et al (2007), the milk from Nero Siciliano sows, a Mediterranean pig genotype like the IB breed, have greater concentrations of fat and energy than IB milk does.…”
Section: My and Compositionmentioning
confidence: 78%